Progression of Sprint Interval Training Set Performance and Physiological Responses during a Six-Week Training Period - Gavriil G. Arsoniadis; Argyris G. Toubekis (Applied Sciences, 2024)
The aim of this study was to examine the progression and the effect of sprint interval training (SIT) on swimmers’ performance and physiological responses during and after a 6-week period. Eight swimmers (age: 16.7 ± 4.2 years) performed maximum efforts for (a) 200 and 400 m front crawl for the determination of critical speed (CS), (b) four 50 m repetitions (4 × 50 m) and a 100 m test before (Pre) and after (Post) the 6-week training period. SIT was applied three times per week including two sets of 4 × 50 m sprints starting every 2 min. Pre and Post swimming time (T), blood lactate (BL), heart rate (HR), and rate of perceived exertion (RPE) were evaluated. CS increased by 4.4 ± 5.2% (p = 0.01) after 6 weeks. The Pre vs. Post values of T in 4 × 50 and 100 m and BL were unchanged (T: d = 0.05, 0.09, p = 0.14, 0.47, respectively; BL: d = 0.12, p = 0.42), while HR was decreased (d = 0.24, p = 0.04). The progression of T in 4 × 50 m training sprints was unchanged (p = 0.25) while BL increased in weeks 3 (9.4 ± 5.9%) and 5 (13.9 ± 7.8%) compared to week 1 (p = 0.01). SIT improved the swimmers’ aerobic endurance. The lactate response progressively increased despite similar SIT performance during the 6-week period.